THE INFLUENCE OF FIELDWORK PRACTICE AND STUDENT JOB INTEREST ON STUDENT WORK READINESS - Mohamad Ikhwan Nur Rosyid; Yelma Dianastiti (STKIP PGRI TULUNGAGUNG, 2023)
This study aims to analyze: (1) the effect of fieldwork practice on students' work readiness; (2) the effect of work interest on students' work readiness; and (3) the effect of fieldwork practice and work interest together on students' work readiness. The sample in this study was 60 students. Sampling research using a proportional random sampling technique. Data collection methods in this study used questionnaires and documentation. Technique analysis of data used is normality test, linearity test, multicollinearity test, and heteroscedasticity test. While for hypothesis testing using t test and f test. The results of this study show: (1) there is a positive and significant effect of fieldwork practice on student work readiness with the results (tcount ttable = 2.987 2.002), (2) there is a positive and significant effect of student work interest on student work readiness with the results (tcount ttable = 7, 294 2.002), and (3) there is a positive and significant effect of fieldwork practice and student work interest together on student work readiness with the results (fcount ftabel = 28.377 3.115).